Bioconversion Of Synthesis Gas To Ethanol In A CSTR. - Najafpour, Ghasem; Younesi, Habiboallah; Mohamad, Abdul Rahman; Kamaruddin, Azlina Harun (2003)
The depletion sources of fossil fuels and chemical feedstock, also the oil crisis in 70’s had drawn the world to find alternative clean renewable resources. The production of fuel by microbial culture was considered as an alternative source.